(untitled) (Revista de História Regional, 2007)
This modest study, for its obliged briefness, will centre on a very concrete period of the republican experience in Spain, included between the proclamation of the Second Spanish Republic on April 14, 1931 and the arrival to the power of the right by virtue of the general celebrated elections on November 19, 1933. It is the stage of government of the conjunction republican - socialist headed by Manuel Azaña and called by it and for the social tackled reforms social period of Azaña. We will not limit to doing to us a simple review of historical events, but we will centre our study in to uncover social and economic root of these years especially and of the whole epoch in general, in order to bring the reader over to the general context and to a propedeutical vision of the period that can be overcome in subsequent works.